Study of the influence of the interfaces on the properties of devices based on La1−xSrxMnO3 (2014)
Abstract. Developing devices to save information, like the magnetoresistive random access memories (MRAM), is a wide area of research now days. The manganites are among those materials to be used for this purpose. The parent compound is the LaMnO3 which can be doped with a divalent alkaline earth metal (i.e. Sr, Ca, Ba) replacing some of the La and leading to a valence mixture (+3 and +4) of the Mn ions. In this thesis some aspects of the fabrication of devices based on the manganite La1−xSrxMnO3 (LSMO), have been studied. To approach this research, it was taken into account the rich phase diagram of the LSMO with the doping x. It is known that the LSMO with x = 0:33 (optimal doping) is ferromagnetic with a Curie temperature, TC, near to 370K (bulk), meanwhile as the value of x increases the TC decreases and around x = 0:55 the LSMO becomes antiferromagnetic. In chapter 2 some results on the behavior of the resistivity of LSMO thin films with optimal doping for different sample thicknesses are presented. Usually, the manganite films show a characteristic metal/insulator (MI) transition at a temperature called Tp that is near to the temperature of the magnetic transition, TC from ferromagnetic to paramagnetic. The films for this thesis, grown on SrTiO3 (STO) by ozone assisted molecular beam epitaxy (MBE), systematically do not show the MI transition, at least up to the highest measurement temperature ~500K. Moreover, even in films grown by the same method but on NdGaO3, NGO, neither such transition was found up to around 400K. Additionally, attempts to fabricate microstructures (wires) by Ar-plasma etching from LSMO films, turned to be efective for those with thickness less or close to 40 u.c. (16nm), but not for thicker ones (~32nm). In chapter 3, the first fabricated magnetic tunneling junctions, MTJ, were based on trilayers of LSMO/STO/LSMO/ (from top to bottom) on STO substrates. The tunneling magnetoresistance, TMR, as a function of the applied magnetic field gave a highest value of 30% at the lowest temperature. It is worthy to recall that the change in the resistance of TMJ takes place when the magnetizations of the ferromagnetic electrodes become antiparallel one to each other. In order to improve the TMR it is necessary a significant difference between the coercive fields of the LSMO electrodes. This can be achieved by the exchange bias effect to pin the magnetization of one of the LSMO films. In chapter 4, the exchange bias effect in F/AF LSMO bilayers was studied by measuring the hysteresis curves at different temperatures after field cooling down to 50K. From these results, the influence of the F-layer thickness, tF , on the exchange field HEB and on the coercive field was studied while keeping the same thickness of the AF layer. Besides, the dependence of the bilayer magnetization on the temperature was also measured. MTJ prepared from multilayers of LSMO(F)/STO(barrier)/LSMO(F)/LSMO(AF)/STO(substrate) (it is worth noting that exchange bilayer F/AF was included) are discussed in chapter 5. For these devices the TMR increased substantially up to 300% at 10K. Moreover, it was found that this value depends on the direction of the applied magnetic field relative to the junction, so that it was possible to obtain values up to 900% or even up to 1900%. Finally, two chips with exchange bias exchange bias were grown on NGO substrates. In the first chip, the MTJ with highest TMR at 10K reach values of around 350%, however it did show a different from zero TMR up to 320K. In the second chip, grown under oxygen pressure, a dependence of the TMR on the excitation current was found. The highest magnetoresistance value was around 1200% (10K). For this junction the dependence of its TMR on the temperature was also studied. The films and multilayers for this thesis were grown by the OXY-MBE group at the IOM, and these were used for the fabrication of wires and junctions which were also characterized by the author of this document. Due to the fact that the layer thicknesses were less than 100nm, the role played by the interfaces is mainly addressed in chapters 4 and 5. The most important results, in the development of this thesis, are summarized at the end of each chapter.